O ensino médio nas atuais políticas educacionais: em busca de uma identidade - Cruvinel, Janaina Junqueira Valaci (2018)
The Master's dissertation analyzes the context of policies for Basic Education in order to show the debate regarding High School, considering the socio-historical context of these policies in the period from 2007 to 2015, as set forth in the last Law of Directives and Bases of National Education until the conclusion of the National Pact for the Strengthening of High School. It is a documentary research that has as its corpus the legislation pertinent to the educational policies for High School. It also includes bibliographical research based on the reading and analysis of books, scientific articles, dissertations and theses that address the High School and the policies for this stage of Basic Education. It develops a dialogue between the bibliography consulted and the documentary corpus, contributed in the categories of analysis: “High School”, “educational policies” and “world of work”, which support the questions raised and the possibilities of answers that were found in the three chapters that make up the dissertation. The interpretation made through the course of this work has the objective of answering the problematizing question: What conceptions of High School are presented in the government programs and how is this stage of education in the context of the policies for Basic Education in the period from 1996 to 2015? It aims, therefore, to understand the role of High School in the context of Brazilian policies for Basic Education, from 2007 to 2015. Based on a historical-critical perspective, the results indicate that there is a strong government policy in Brazil regarding the discontinuation of educational policies. With respect to High School, the obscurity present regarding High School has been evident since its implantation in Brazil, and in terms of identity of this stage of basic education, pointed out by the indices that mark the precariousness of High School. We conclude that the lack of understanding about the different youths that compose the different forms of High School in Brazil contributes greatly to the difficulty of implementing policies that meet the needs of the young public. This study is relevant in view of the current political situation in which the country is going through, in a frank struggle of forces on whether or not to implement a new restructuring of High School.